Remotely controlled mindstorm nxt vehicle using bluetooth communication - Obot, E. I. (ХНУРЕ, 2019)
This paper presents the remote control of the Lego car using a personal computer (PC) via Bluetooth communication. The system presented here consists of a PC, a Lego MINDSTORMS car, and a program to be run on the PC to connect to the Lego MINDSTORMS car and to send commands to the Lego car. This program is written in Java on leJOS NXJ. An Android smartphone is used to capture the view in front of the robot. It mounted in the holder streams video through the Internet, so it can be viewed in real-time on the PC. The purpose of this paper is the development a small scale remote controlled vehicle using a Bluetooth communication and vision system from the idea to the final testing.